2013
DOI: 10.4102/hts.v69i1.2001
|View full text |Cite
|
Sign up to set email alerts
|

Reading and proclaiming the Birth Narratives from Luke and Matthew: A study in empirical theology amongst curates and their training incumbents employing the SIFT method

Abstract: Drawing on Jungian psychological type theory, the SIFT method of biblical hermeneutics and liturgical preaching suggests that the reading and proclaiming of scripture reflects the psychological type preferences of the reader and preacher. This thesis is examined amongst two samples of curates and training incumbents (N = 23, 27), serving in one Diocese of the Church of England, who completed the Myers-Briggs Type Indicator. Firstly, the narrative of the shepherds from Luke was discussed by groups organised acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 9 publications
0
21
0
Order By: Relevance
“…The analogy is with human handedness where most people develop their skills with one hand, to the comparative neglect of the other (cf. Francis & Smith 2013).…”
Section: Psychological Type Theorymentioning
confidence: 95%
See 2 more Smart Citations
“…The analogy is with human handedness where most people develop their skills with one hand, to the comparative neglect of the other (cf. Francis & Smith 2013).…”
Section: Psychological Type Theorymentioning
confidence: 95%
“…Thus, dominant sensing shapes the practical person, dominant intuition shapes the creative and imaginative person, dominant thinking shapes the strategic and logical person, and dominant feeling shapes the caring and humane person (cf. Francis & Smith 2013).…”
Section: Psychological Type Theorymentioning
confidence: 95%
See 1 more Smart Citation
“…A significant contribution to the application of psychological type theory for understanding the dynamics of clergy was made by Oswald and Kroeger (1988) in their book, Personality type and religious leadership. More recently a series of empirical studies conducted among clergy has illuminated the connections between individual differences in psychological type and a number of areas of clergy practice and experience, including: ministry styles (Francis & Payne, 2002;Fawcett, Francis, & Robbins, 2011), preaching styles (Francis, 2010;Francis & Jones, 2011;Francis, 2012a, Francis, 2012b, Francis 2013Francis & Smith, 2013), and work-related psychological health (Francis, Wulff, & Robbins, 2008;Francis, Robbins, Kaldor, & Castle, 2009;Robbins & Francis, 2010;Brewster, Francis, & Robbins, 2011;Francis, Gubb, & Robbins, 2012;Robbins, Francis, & Powell, 2012;Francis, Payne, & Robbins, 2013.…”
Section: Introductionmentioning
confidence: 99%
“…These studies have examined the feeding of the five thousand in Mark 6: 34-44 (Francis, 2010) 8-16 (Francis & Smith, 2013). These empirical studies found the predicted differences in sensing, intuition, thinking and feeling readings of the same text.…”
Section: Psychological Type Theory As Empirical Theologymentioning
confidence: 99%